Marine pharmacognosy trends and applications - Kim, Se-Kwon. (Boca Raton : Taylor & Francis, 2012)
"Marine pharmacognosy is a dynamic field that has been systematically investigated over the last 50 years. The potential of the field is shown by the number of publications and the patents that are constantly increasing every year. This book presents the latest comprehensive studies of marine derived medicinal substances for biological, medical and industrial applications. Marine flora and fauna has been the source of molecules used as pharmaceuticals, cosmeceuticals, nutraceuticals, molecular probes, fine chemicals and agrochemicals. Bringing together a global author team of experts, this text provides a current snapshot of the importance of marine products in health formulation"--Provided by publisher.
ch. 1. Past, present, and future of marine pharmacognosy / Se-Kwon Kim -- ch. 2. Antidiabetic compounds from marine organisms and their properties / Miyuki Shirosaki and Tomoyuki Koyama -- ch. 3. Bioactive compounds from Okinawan marine cyanobacteria / Toshiaki Teruya, Osamu Ohno, and Kiyotake Suenaga -- ch. 4. Bioactive secondary metabolites from marine-derived fungi / Sherif S. Ebada and Peter Proksch -- ch. 5. Cytotoxic briarane-type diterpenoids / Yonghong Liu ... [et al.] -- ch. 6. Pharmacoanalytical procedures for chondroitin present in raw materials and biological fluids / Bradley Wright and Brian Lockwood -- ch. 7. Marine natural products targeting nuclear factor KB / U. Sebnem Harput -- ch. 8. The immunomodulatory effect of marine algae on allergic response / Se-Kwon Kim, Thanh-Sang Vo, and Dai-Hung Ngo -- ch. 9. Pharmacological effects of marine-derived bioactive peptides / Se-Kwon Kim ... [et al.] -- ch. 10. Sea cucumber saponins : realization of their anticancer effects / Se-Kwon Kim, S.W.A. Himaya, and Kyong-Hwa Kang -- ch. 11. Phlorotannins as potential antibacterial agents from marine brown algae / Sung-Hwan Eom and Se-Kwon Kim -- ch. 12. Bioactive molecules from symbiotic marine dinoflagellates / Masaki Kita ... [et al.] -- ch. 13. Pharmacological potential of phlorotannins from marine brown algae / BoMi Ryu and Se-Kwon Kim -- ch. 14. Microalgae as sources of biomaterials and pharmaceuticals / Kyong-Hwa Kang and Se-Kwon Kim -- ch. 15. Marine ascidians : a promising resource for bioactive compounds / H. Abdul Jaffar Ali and M. Tamilselvi -- ch. 16. Chitosan and its derivatives for treatment of diabetic complications / Se-Kwon Kim and Fatih Karadeniz -- ch. 17. Alkaloids as pharmaceutical agents from marine fungi / Se-Kwon Kim and Yong-Xin Li -- ch. 18. Pharmacological effects and prospects of marine algae in promoting women's health and longevity / Se-Kwon Kim, Ratih Pangestuti, and A. B. Susanto -- ch. 19. Marine sponge-associated microbes : a source of biologically active metabolites / Se-Kwon Kim, Pradeep Dewapriya, and Yong-Xin Li -- ch. 20. Marine actinobacteria : a potential source of antifungal compounds / R. Vijayakumar, A. Panneerselvam, and N. Thajuddin -- ch. 21. Marine drugs : treatment for osteoporosis and related bone diseases / Jayachandran Venkatesan and Se-Kwon Kim -- ch. 22. Bioactive compounds from marine sources for gastrointestinal cancer treatment / Se-Kwon Kim and Mustafa Zafer Karagozlu -- ch. 23. Marine algae : pharmacological values and anti-inflammatory effects / Se-Kwon Kim, Thanh-Sang Vo, and Dai-Hung Ngo -- ch. 24. Marine microbial pharmacognosy : aspects and prospects / Se-Kwon Kim and Ira Bhatnagar -- ch. 25. Pharmacognosy prospects of marine algal derivatives in the management of skin inflammation / Se-Kwon Kim and Noel Vinay Thomas -- ch. 26. Antidiabetic effect of dieckol, a marine polyphenol, and its mechanisms of blood glucose regulation / Seung-Hong Lee and You-Jin Jeon -- ch. 27. Allergy and its remedies from marine sources / Ramjee Pallela ... [et al.] -- ch. 28. Anticancer mechanisms of actin depolymerization agent pectenotoxin-2 / Gi-Young Kim and Yung Hyun Choi -- ch. 29. Marine mucin : a prospective cosmetic and pharmaceutical / Se-Kwon Kim, Fatih Karadeniz, and Mustafa Zafer Karagozlu -- ch. 30. Neuropharmacological properties of marine plants / Suengmok Cho and Se-Kwon Kim -- ch. 31. Antiparasitic secondary metabolites from marine actinobacteria / D. Dhanasekaran, N. Thajuddin, and A. Panneerselvam -- ch. 32. Pharmaceutical aspect of metabolites from marine algae on skin health / Jung-Ae Kim and Se-Kwon Kim -- ch. 33. Clues for cancer from ocean-derived molecules and role of in silico techniques in anticancer drug discovery / G. Dicky John Davis, Veeresh Kumar Sali, and Hannah R. Vasanthi -- ch. 34. Anticancer compounds from marine microorganisms / Hee Jae Shin.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Marine biology; Pharmacognosy; Electronic books